Get comprehensive solutions to your questions with the help of IDNLearn.com's experts. Our platform is designed to provide trustworthy and thorough answers to any questions you may have.

Enter the correct answer in the box.

If [tex]$x \neq 0$[/tex], what is the sum of [tex]$4 \sqrt[3]{x^{10}} + 5 x^3 \sqrt[3]{8 x}$[/tex] in simplest form?


Sagot :

To find the sum of [tex]\(4 \sqrt[3]{x^{10}} + 5 x^3 \sqrt[3]{8 x}\)[/tex] in simplest form, let's break it down step-by-step and simplify each term separately.

1. Simplify the first term [tex]\(4 \sqrt[3]{x^{10}}\)[/tex]:

[tex]\[ 4 \sqrt[3]{x^{10}} \][/tex]

The cube root of [tex]\(x^{10}\)[/tex] can be written as:

[tex]\[ \sqrt[3]{x^{10}} = (x^{10})^{1/3} = x^{10/3} \][/tex]

So, the first term becomes:

[tex]\[ 4 \sqrt[3]{x^{10}} = 4 \cdot x^{10/3} = 4 x^{10/3} \][/tex]

2. Simplify the second term [tex]\(5 x^3 \sqrt[3]{8 x}\)[/tex]:

[tex]\[ 5 x^3 \sqrt[3]{8 x} \][/tex]

The cube root of [tex]\(8 x\)[/tex] is:

[tex]\[ \sqrt[3]{8 x} \][/tex]

We know that [tex]\(8\)[/tex] can be written as [tex]\(2^3\)[/tex], so:

[tex]\[ \sqrt[3]{8 x} = \sqrt[3]{2^3 \cdot x} = 2 \cdot \sqrt[3]{x} = 2 x^{1/3} \][/tex]

Therefore, the second term becomes:

[tex]\[ 5 x^3 \cdot \sqrt[3]{8 x} = 5 x^3 \cdot 2 x^{1/3} = 10 x^{3 + 1/3} = 10 x^{10/3} \][/tex]

3. Combine the simplified terms:

Now, sum the two simplified terms:

[tex]\[ 4 x^{10/3} + 10 x^{10/3} \][/tex]

These are like terms and can be added together:

[tex]\[ = (4 + 10) x^{10/3} \][/tex]

[tex]\[ = 14 x^{10/3} \][/tex]

Thus, the simplest form of [tex]\(4 \sqrt[3]{x^{10}} + 5 x^3 \sqrt[3]{8 x}\)[/tex] is:

[tex]\[ 14 x^{10/3} \][/tex]